2012
DOI: 10.1371/journal.pone.0032998
|View full text |Cite
|
Sign up to set email alerts
|

Creating Non-Believed Memories for Recent Autobiographical Events

Abstract: A recent study showed that many people spontaneously report vivid memories of events that they do not believe to have occurred [1]. In the present experiment we tested for the first time whether, after powerful false memories have been created, debriefing might leave behind nonbelieved memories for the fake events. In Session 1 participants imitated simple actions, and in Session 2 they saw doctored video-recordings containing clips that falsely suggested they had performed additional (fake) actions. As in ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
93
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 65 publications
(105 citation statements)
references
References 21 publications
6
93
2
Order By: Relevance
“…In sum, whereas Clark et al (2012) and Otgaar et al (2013) demonstrate the importance of distinguishing between remembering and believing when studying autobiographical memory (Mazzoni & Kirsch, 2002), the final demonstration of the independence between the belief in the occurrence of an event and the memory for that same event requires showing that it is possible to substantially decrease individuals' belief in the occurrence of vividly remembered events that genuinely occurred. The present study aimed at producing such a demonstration by providing participants with negative misinformation RUNNING HEAD: NON-BELIEVED TRUE MEMORIES 8 about the occurrence of true events; that is, by falsely claiming that those events never occurred.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations
“…In sum, whereas Clark et al (2012) and Otgaar et al (2013) demonstrate the importance of distinguishing between remembering and believing when studying autobiographical memory (Mazzoni & Kirsch, 2002), the final demonstration of the independence between the belief in the occurrence of an event and the memory for that same event requires showing that it is possible to substantially decrease individuals' belief in the occurrence of vividly remembered events that genuinely occurred. The present study aimed at producing such a demonstration by providing participants with negative misinformation RUNNING HEAD: NON-BELIEVED TRUE MEMORIES 8 about the occurrence of true events; that is, by falsely claiming that those events never occurred.…”
Section: Introductionmentioning
confidence: 96%
“…Although the Clark et al (2012) and Otgaar et al (2013) studies provide compelling demonstrations that experimentally created beliefs in false events can be easily undermined, they do not show that beliefs can be dissociated from true memories. Indeed, findings from many domains of psychology show subtle ways in which true and false memories can differ.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The second form of evidence comes from recent studies of non-believed memories. In those studies, researchers were able to use persuasive techniques to undermine participants' beliefs in the truthvalue of their memories, without fully undermining the memories themselves (Clark, Nash, Fincham, & Mazzoni, 2012;Mazzoni et al, in press;Otgaar, Scoboria, & Smeets, 2013). These authors showed that the persuasive techniques left behind 'nonbelieved' memory content that shared many of the same subjective and experiential characteristics as believed memories.…”
Section: From Memory To Beliefmentioning
confidence: 99%